PROTOTYPE SISTEM MONITORING DAN CONTROLLING BUDIDAYA MICROGREEN DENGAN MENGGUNAKAN WEBSITE BERBASIS INTERNET OF THINGS (IoT) - Sadih Saputra; Ariep Jaenul; Arisa Olivia (Universitas Nusa Cendana, 2022)
The increase in population impacts the limited land for growing crops since it establishes residential areas. The Organic plants for human consumption also increase following population growth. A microgreen is one of some techniques in agriculture to overcome this problem. In this research, a monitor and control system was constructed for microgreen cultivation and integrated into a website through an internet connection. This system uses a DHT11 sensor as a temperature and humidity sensor in the plant environment, a soil moisture sensor as a plant media humidity sensor, and RTC DS3231 as time control. The sensor output should be processed by the Arduino Mega 2560 microcontroller and forwarded to the actuators automatically. This prototype will be able to reduce the air temperature by 3.65 ºC and maintain the humidity of the growing media to 43%. The outcome of this prototype showed that it could increase the growth of microgreens 8 cm long in 14 days.